Fungsi Sel Imun Interleukin-4 (IL-4) pada Ikan Kerapu Tikus (Cromileptes altivelis) dengan Induksi Protein Imunogenik Vibrio harveyi [The Function Of Interleukin-4 (IL-4) Immune Cells On Humpback Grouper (Cromileptes altivelis) By Induction Of Immunogenic Protein Of Vibrio harveyi ] - Uun Yanuhar; Asus Maizar SH; Ita Fitria S (Faculty of Fisheries and Marine Universitas Airlangga, 2012)
Abstract Humpback grouper (Cromileptes altivelis) is a commodity to be cultivated because it has a high price, but the grouper highly susceptible to Vibriosis (Vibrio harveyi). The research objective was to see the function of immune cells of interleukin-4 (IL-4) are formed due to the induction of immunogenic proteins of Vibrio harveyi. Research procedures include Vibrio harveyi immunogenic protein isolation, SDS-PAGE electrophoresis, elektroelusi and dialysis, clinical exam of Vibrio harveyi immunogenic proteins, and immunohistochemical to look at immune cells (cells IL-4) with using a secondary antibody labeling of anti IL-4 biotin conjugate. The results showed that Vibrio harveyi protein found have immunogenic properties is 51.16 kDa. This protein is an adhesin protein. Protein 51.16 kDa was purified by electroelution and the protein will be used as a vaccine administered by intraperitoneal injection in grouper (Cromileptes altivelis) at a dose of 31.6 ug protein / 150 g of fish weight. In organ tissues of the brain, eyes and kidneys of induced fish by immunohistochemical examination, It was detected Immune cells (cells IL-4) using a secondary antibody labeling of anti IL-4 biotin conjugate. Tues formed IL-4 can be seen on the network grouper indicated by a change in tissue color with an inverted microscope examination of the golden brown color is formed on the IL-4 immune cells. It show the cross-reaction between 51.16 kDa immunogenic protein induced in fish with anti IL-4 biotin conjugate. The conclusions is the protein of Vibrio harveyi with molecular weight of 51.16 kDa is an immunogenic protein which able to induce formation of IL-4 in grouper.